The Analysis of Figurative Language in Halsey’s Selected Songs Lyric - Reni Nursyanti; Deri Sis Nanda; Dini Dwintika Karuniati; Harpain Harpain (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2020)
Figurative language is a non-literal meaning of sentences or words in order to make attractive languages in written text based on the theory of Aristotle Therefore, this research aims to analyze what kinds of figurative language in Halsey’s selected song which are Colors, The Feeling, Without Me, Haunting, Ghost, Walls Could Talk, and Nightmare. Moreover, the contextual meaning of the selected song’s lyrics is analyzed based on the theory of Halliday. Contextual meaning has three types which are field, tenor, and mode by observing through reading the lyrics from genius.com. The Field and Mode of the songs refer to the culture of the composer lived in, and Tenor is symbol of participation of life objects. The result is in classified and percentage the data. Thus, it concluded and calculated that the seven selected songs of Halsey have 2 items or 13% of allegory, 1 or 6% of conceit, 5 or 31% of hyperbole, 4 or 25% of irony, 2 or 13% of litotes, 8 or 20% of metaphor, 2 or 13% of onomatopoeia, 4 or 25% of personification, 6 or 38% of rhetorical question, 11 or 69% of simile, and 3 or 9% of symbol. The result of this study will be able to give contribution to the readers who are interested in learning and understanding or interpreting those lyrics.